2022
DOI: 10.1186/s12884-022-05141-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oocytes containing smooth endoplasmic reticulum aggregates on assisted reproductive outcomes: a cohort study

Abstract: Background The impact of smooth endoplasmic reticulum aggregates (SERa) on assisted reproductive technology (ART) outcomes was still controversial. Our objective is to investigate the impact of the presence of SERa on intracytoplasmic sperm injection (ICSI) outcomes. Methods This was a retrospective cohort study. A total of 1,090 fresh ICSI cycles from 944 patients between January 2016 and June 2020 were included. Outcomes from clinical, embryologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, patients who have had multiple unsuccessful IVF cycles have been observed to exhibit a recurring presence of SERa; our patient also had a history of two unsuccessful IVF cycles, which may have contributed to the appearance of SERa [ 21 ]. Fang et al [ 22 ] concluded that the presence of SERa in the oocyte resulted in cleavage failure, and according to the above observation, it also affects the cleavage rate in such a way that the cleavage rate of SERa+ oocytes was much lower than the cleavage rate of normal ICSI [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients who have had multiple unsuccessful IVF cycles have been observed to exhibit a recurring presence of SERa; our patient also had a history of two unsuccessful IVF cycles, which may have contributed to the appearance of SERa [ 21 ]. Fang et al [ 22 ] concluded that the presence of SERa in the oocyte resulted in cleavage failure, and according to the above observation, it also affects the cleavage rate in such a way that the cleavage rate of SERa+ oocytes was much lower than the cleavage rate of normal ICSI [ 22 ].…”
Section: Discussionmentioning
confidence: 99%